Prevalence and Antimicrobial Resistance of Escherichia coli, Salmonella and Vibrio Derived from Farm-Raised Red Hybrid Tilapia (Oreochromis spp.) and Asian Sea Bass (Lates calcarifer, Bloch 1970) on the West Coast of Peninsular Malaysia - Rita Rosmala Dewi; Latiffah Hassan; Hassan Mohammad Daud; Mohd. Fuad Matori; Fauziah Nordin; Nur Indah Ahmad; Zunita Zakaria (MDPI AG, 2022)
Antibiotics are widely used in intensive fish farming, which in turn increases the emergence of antimicrobial-resistant (AMR) bacteria in the aquatic environment. The current study investigates the prevalence and determines the antimicrobial susceptibility of E. coli, Salmonella, and Vibrio in farmed fishes on the west coast of Peninsular Malaysia. Over a period of 12 months, 32 aquaculture farms from the Malaysian states of Selangor, Negeri Sembilan, Melaka, and Perak were sampled. Both E. coli and Salmonella were highly resistant to erythromycin, ampicillin, tetracycline, and trimethoprim, while Vibrio was highly resistant to ampicillin and streptomycin. Resistance to the antibiotics listed as the highest priority and critically important for human therapy, such as colistin in E. coli (18.1%) and Salmonella (20%) in fish, is a growing public health concern. The multi-drug resistance (MDR) levels of E. coli and Salmonella in tilapia were 46.5% and 77.8%, respectively. Meanwhile, the MDR levels of E. coli, Salmonella, V. parahaemolyticus, V. vulnificus and V. cholerae in Asian seabass were 34%, 100%, 21.6%, 8.3% and 16.7%, respectively. Our findings provide much-needed information on AMR in aquaculture settings that can be used to tailor better strategies for the use of antibiotics in aquaculture production at the local and regional levels.